Treatment and persistence/recurrence of sleep‐disordered breathing in children with Down syndrome. Issue 8 (6th June 2019) - Nehme, Joy; LaBerge, Robert; Pothos, Mary; Barrowman, Nicholas; Hoey, Lynda; Kukko, Madelaine; Monsour, Andrea; Katz, Sherri L.
Abstract: Objective: Sleep‐disordered breathing (SDB) is common in children with Down syndrome, but the trajectory and long‐term outcomes are not well‐described. In a retrospective longitudinal cohort of children with Down syndrome, study objectives were to (1) characterize polysomnography (PSG), treatments received, and persistence/recurrence of SDB and (2) explore predictors of SDB persistence/recurrence. Methods: A retrospective cohort study was conducted of children who underwent PSGs between 2004 and 2014. SDB was defined as obstructive sleep apnea (OSA)‐mixed (apnea‐hypopnea index [AHI] >5 events/hour), central sleep apnea or hypoventilation. PSGs, interventions, and trajectory of SDB were described. Age, body mass index (BMI) Z ‐score and AHI at first SDB diagnosis were evaluated as predictors of persistent/recurrent SDB. Results: Of 506 children, 120 had ≥1 PSG; 54 had subsequent PSGs. Children with ≥2 PSGs were more likely to have higher total AHI ( P = .02) and obstructive‐mixed AHI ( P = .01). Thirty‐five of fifty‐four (65%) were initially diagnosed with OSA‐mixed SDB. After first PSG, 67 of 120 had OSA‐mixed SDB, of whom 25 (37.3%) underwent adenotonsillectomy (T&A), 13 (19.4%) received positive airway pressure (PAP). Those who underwent T&A after PSG were significantly younger than those who received PAP (median age 6.2 vs 12.5 years; P = .005). OSA‐mixed SDB persisted/recurred in 33 of 54 (73.3%) with ≥2 PSGs. Persistence/recurrence was not associated with age, AHI or BMI Z ‐score at first SDB. Conclusion: Children with Down syndrome undergoing T&A for SDB were significantly younger than those treated with PAP. SDB persisted/recurred in three of four and was not predicted by age, SDB severity or BMI Z ‐score. Longitudinal PSG assessment for persistence/recurrence of SDB is required in this population.